#### Answer

18y - 6

#### Work Step by Step

6y + 12y - 6 =
y $\times$ (6 + 12) - 6 =
y $\times$ 18 - 6
18y - 6

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

18y - 6

6y + 12y - 6 =
y $\times$ (6 + 12) - 6 =
y $\times$ 18 - 6
18y - 6

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.